MP43: Evaluation of undergraduate point of care ultrasound instruction in a rural Canadian medical school. (May 2019) - Kuehner, Z.; Dmitriew, M.; Jefkins, M.; Piper, B.; Byce, S.; Dubois, S.; Zanette, C.
Abstract : Introduction : Point of care ultrasound is a burgeoning tool in clinical medicine and its utility has been demonstrated in a variety of contexts. It may be especially useful in rural areas where access to other imaging equipment (such as CT) is limited. However, there exists debate about the utility of teaching ultrasound theory and technique to medical undergraduates, particularly those in their first two years of study. This study evaluated the efficacy of teaching undergraduate-tailored ultrasound training sessions to first and second-year medical students at the Northern Ontario School of Medicine (NOSM), a rural-focused medical institution.Methods : Sixty students participated in tailored ultrasound teaching sessions that involved both lecture and hands-on components. Participating students were assessed following each session, as well as at study completion, in terms of ultrasound knowledge, anatomy, pathology, orientation, and interpretation of computerized tomography (CT) scans (transferability). Participants' performance was measured against a control group of their peers. Program evaluation was completed using Likert-type scales to determine participant comfort with ultrasound before and after the training, and areas of strength and improvement.Results : Participating students showed statistically significant improvement in ultrasound interpretation and anatomical orientation with trends toward improved anatomy and pathology knowledge, and ability to interpret computerized tomography (CT) scans compared to controls. Students participating in the course expressed improved comfort with ultrasound techniques and desire for future integration of ultrasound into their training, but noted that increasing frequency of training sessions might have improved retention and confidence.Conclusion : Results suggest that using an undergraduate-focused and system-specific ultrasound training course yields retention in ultrasound interpretation ability and objective improvement in relational anatomy knowledge. Trends toward improvement in general anatomy, pathology and CT interpretation suggest areas of future study.